Effects of elevated CO2 and N addition on growth and N2 fixation of a legume subshrub (Caragana microphylla Lam.) in temperate grassland in China. - Lin Zhang; Dongxiu Wu; Huiqiu Shi; Canjuan Zhang; Xiaoyun Zhan; Shuangxi Zhou (PLoS ONE, 2011)
It is well demonstrated that the responses of plants to elevated atmospheric CO(2) concentration are species-specific and dependent on environmental conditions. We investigated the responses of a subshrub legume species, Caragana microphylla Lam., to elevated CO(2) and nitrogen (N) addition using open-top chambers in a semiarid temperate grassland in northern China for three years. Measured variables include leaf photosynthetic rate, shoot biomass, root biomass, symbiotic nitrogenase activity, and leaf N content. Symbiotic nitrogenase activity was determined by the C(2)H(2) reduction method. Elevated CO(2) enhanced photosynthesis and shoot biomass by 83% and 25%, respectively, and the enhancement of shoot biomass was significant only at a high N concentration. In addition, the photosynthetic capacity of C. microphylla did not show down-regulation under elevated CO(2). Elevated CO(2) had no significant effect on root biomass, symbiotic nitrogenase activity and leaf N content. Under elevated CO(2), N addition stimulated photosynthesis and shoot biomass. By contrast, N addition strongly inhibited symbiotic nitrogenase activity and slightly increased leaf N content of C. microphylla under both CO(2) levels, and had no significant effect on root biomass. The effect of elevated CO(2) and N addition on C. microphylla did not show interannual variation, except for the effect of N addition on leaf N content. These results indicate that shoot growth of C. microphylla is more sensitive to elevated CO(2) than is root growth. The stimulation of shoot growth of C. microphylla under elevated CO(2) or N addition is not associated with changes in N(2)-fixation. Additionally, elevated CO(2) and N addition interacted to affect shoot growth of C. microphylla with a stimulatory effect occurring only under combination of these two factors.